2013
DOI: 10.5489/cuaj.268
|View full text |Cite
|
Sign up to set email alerts
|

Parameters predicting postoperative unilateral disease in patients with unilateral prostate cancer in diagnostic biopsy: a rationale for selecting hemiablative focal therapy candidates

Abstract: E82Cite as: Can Urol Assoc J 2013;7:E82-E87. http://dx.doi.org/10.5489/cuaj.268. Epub 2011 November 2. AbstractBackground: Focal hemiablative therapy for prostate cancer is a new treatment alternative. Unilateral and unifocal disease are its main limitations. The aim of this study was to identify the epidemiological, clinical and pathological parameters that may predict unilateral disease in patients diagnosed with prostate cancer. Methods:We performed a retrospective analysis of patients at our institution be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 27 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…10 In our report, a positive biopsy at the apex was a predictor of contralateral disease. In fact, the apex represents a much smaller proportion of the gland than the mid and base regions.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…10 In our report, a positive biopsy at the apex was a predictor of contralateral disease. In fact, the apex represents a much smaller proportion of the gland than the mid and base regions.…”
Section: Discussionsupporting
confidence: 49%
“…Few studies have focused on the reliability of unilaterally positive biopsies to adequately predict the presence of less invasive disease to the contralateral side. [8][9][10] On the basis of these considerations, we assessed the incidence of bilateral disease, contralateral EPE (cEPE), and contralateral positive surgical …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] Two of these studies reported on the rate of bilateral csCaP on WMP (33% and 50%, respectively) in patients with only unilateral disease on TRUS biopsy alone. [11][12][13][14][15][16][17][18] Two of these studies reported on the rate of bilateral csCaP on WMP (33% and 50%, respectively) in patients with only unilateral disease on TRUS biopsy alone.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Although there is strong clinical evidence that prostate imaging with mpMRI and targeted biopsy improves csCaP detection on the patient level, [18][19][20][21][22][23] to our knowledge the detection sensitivity for mpMRI for individual CaP foci remains moderate, particularly in smaller, nonindex, multifocal lesions. Appropriate candidates for hemiablation have csCaP limited to 1 prostate lobe.…”
Section: Introductionmentioning
confidence: 99%
“…However, cases with significant PCa were not listed and, like Sinnott et al, cases with Gleason ≥8 on PB were included. Sfoungaristos et al [20] analysed 161 RP for unilateral PCa in a series of at least sextant biopsy, with unilateral disease at final RP in 28% but, in this case, neither significant PCa nor the IL were analysed. In summary, we consider that TRUS-guided random 12-core prostate biopsy fails to detect the presence of significant PCa foci or the IL itself.…”
Section: Discussionmentioning
confidence: 99%